2020
DOI: 10.1016/j.ecoinf.2020.101174
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of machine learning and sampling frequency on phytoplankton bloom forecasts in coastal areas

Abstract: In aquatic ecosystems, anthropogenic activities disrupt nutrient fluxes, thereby promoting harmful algal blooms that could directly impact economies and human health. Within this framework, the forecasting of the proxy of chlorophyll a in coastal areas is the first step to managing these algal blooms. The primary goal was to analyze how phytoplankton bloom forecasts are impacted by different sampling frequencies, by using a machine learning model. The database used in this study was sourced from an automated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
4
11
0
Order By: Relevance
“…Sampling frequency has widely been recognized as having significant impacts on various analyses (e.g., Lehtiniemi et al, 2022;Ma et al, 2022), and yet sampling frequencies are commonly too low (Estes et al, 2018). The implications for ecological forecasting are not well known, as we are aware of few and contrasting findings regarding the effects of sampling frequency on forecasting (Derot et al, 2020;Wauchope et al, 2019), and which potentially were influenced by sample sizes. We found that lowering the sampling frequency worsened the abundance forecasts for 11 out of the 12 targets.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling frequency has widely been recognized as having significant impacts on various analyses (e.g., Lehtiniemi et al, 2022;Ma et al, 2022), and yet sampling frequencies are commonly too low (Estes et al, 2018). The implications for ecological forecasting are not well known, as we are aware of few and contrasting findings regarding the effects of sampling frequency on forecasting (Derot et al, 2020;Wauchope et al, 2019), and which potentially were influenced by sample sizes. We found that lowering the sampling frequency worsened the abundance forecasts for 11 out of the 12 targets.…”
Section: Discussionmentioning
confidence: 99%
“…Waterbodies must maintain a good chemical and ecological status to protect human health and safeguard natural ecosystems. Nutrients are important indicators that affect water quality, watershed health, and biological processes [ 1 , 2 ]. As key constituents of riverine nutrients, high concentrations of nitrogen (N) and phosphorus (P) may lead to eutrophication and anoxia in coastal waters [ 3 ], thereby not only affecting the living environment of human beings but also the biodiversity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not just hyperparameter and model structure, data input associated with different sampling frequencies might also induce uncertainties and influence estimation accuracy [ 37 ]. Derot et al [ 2 ] demonstrated that the different sampling frequency datasets directly impact the forecast performance of an RF model. According to their findings, the accuracy of phytoplankton bloom forecasts for a 20-min time step was higher than that of the 1-day time step.…”
Section: Introductionmentioning
confidence: 99%
“…In case of binary classification (bloom/no bloom), the final result is the most "popular" class, i.e., the output for the majority of trees [41]. RF has been extensively used in ecological modelling [42][43][44], and during the last years, it has been successfully employed to HAB prediction [15,26,28,[45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%